IMPLEMENTASI PROGRAM ALOKASI DANA DESA (ADD) DI DESA DODA KECAMATAN LORE TENGAH KABUPATEN POSO - Woiya, Krisnawati (Katalogis, 2018)
This   study   aimed   to   determine   the   implementation   of   Village   Fund Allocation   (Alokasi   Dana   Desa  -  ADD)  Policy  in   Doda Village   Central  Lore District Poso Regency. The method used in this study was qualitative method in which the main instrument in this study was the researcher itself. The data used were primary and secondary data relating to the empirical situation and condition of   the   policy  implementation.  This   study  used  the theory of   Edward  III. The results showed that the implementation of Village Fund Allocation Policy in Doda Village   Central   Lore   District   Poso   Regency   had   not   been   running   optimally because it was showed that from the 4 (four) aspects studied, there were two (2) aspects that were not running well, namely the communication aspect, (lack of socialization)   and   the   resources   aspect   (inadequate   human   resources   and infrastructures), while the two (2) aspects that had been running well enough were the   aspect   of   implementers   disposition   (enough   to   support   the   policy implementation)   and   the   aspect   of   the   bureaucratic   structure   (where   all   the implementers had been working in accordance with the duties and functions of each).